STRATEGI PARTAI GERAKAN INDONESIA RAYA (GERINDRA) DALAM MENINGKATKAN PEROLEHAN SUARA PADA PEMILU LEGISLATIF TAHUN 2014 DI KOTA PEKANBARU - Rachmad Prawira. A.C; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
In the 2014 legislative elections last year, an increase in the acquisition of a very significant noise experienced by Indonesia Movement Party in Pekanbaru., As seen in the comparison of votes Great Indonesia Movement Party in 2009 which won 2.22% of the vote, whereas in 2014 Indonesia Movement Party gained 9.49% increase in noise is.Political facts above, the key problem that arises in this study is what the Great Indonesia Movement Party strategy to improve the sound in the legislative elections in 2014 in the city of Pekanbaru. This study used a qualitative approach that is intended to collect the data as much as possible and the facts are then taken to a conclusion.Great Indonesia Movement Party strategy to increase the number of votes in the legislative elections of the most dominant Pekanbaru is through recruiting qualified candidates, engage with the community, doing useful activities such as gymnastics, mutual cooperation, pemasagan banners and billboards and deliver material quality. And do not forget to also sell the name Prabowo As chairman of the General and the President of the Republic of Indonesia candidates.Keywords: Strategy, Political Party, Gerindra